The effect of combining green iron nanoparticles and algae on the sustainability of broiler production under heat stress conditions - Almeldin, Yousri A. R.; Eldlebshany, Amira E.; Elkhalek, Enass Abd; Abdel-Wareth, Ahmed A. A.; Lohakare, Jayant (Frontiers in Veterinary Science, 2024)
Background Natural feed additives in broiler feed contribute to the overall health, productivity, and economic viability of broiler chickens while meeting consumer demands and preferences for natural products. The purpose of this research was to determine the effect of green iron nanoparticles (Nano-Fe) and Halimeda opuntia supplementation in broiler diets on performance, ammonia excretion in excreta, Fe retention in tissues and serum, carcass criteria, and meat quality under hot environmental conditions. Methods A total of 256 one-day-old male Ross 308 broiler chicks were randomly assigned to one of four feeding treatments for 42 days. Each treatment had eight replications, with eight chicks per replicate. The treatments were Negative control (CON), positive control (POS) supplemented with 1 g/kg Halimeda opuntia as a carrier, POS + 20 mg/kg Nano-Fe (NFH1), POS + 40 mg/kg Nano-Fe (NFH2). Results When compared to CON and POS, dietary Nano-Fe up to 40 mg/kg enhanced (p < 0.001) growth performance in terms of body weight (BW), body weight gain (BWG), and feed conversion ratio (FCR). Nano-Fe had the highest BWG and the most efficient FCR (linear, p < 0.01, and quadratic, p < 0.01) compared to POS. Without affecting internal organs, the addition of Nano-Fe and POS enhanced dressing and reduced (p < 0.001) abdominal fat compared to control (CON). Notably, the water-holding capacity of breast and leg meat was higher (p < 0.001), and cooking loss was lower in broilers given Nano-Fe and POS diets against CON. In comparison to POS, the ammonia content in excreta dropped linearly as green Nano-Fe levels increased. When compared to CON, increasing levels of Nano-Fe levels boosted Fe content in the breast, leg, liver, and serum. The birds fed on POS showed better performance than the birds fed on CON. Conclusion Green Nano-Fe up to 40 mg/kg fed to broiler diets using 1 g/kg Halimeda opuntia as a carrier or in single can be utilized as an efficient feed supplement for increasing broiler performance, Fe retentions, carcass characteristics, meat quality, and reducing ammonia excretions, under hot conditions.